The working environment and living condition of foreign migrant workers in Malaysia - Hamid, Zarinah; Abdullah, Moha Asri; Zainuddin, Zaiti Akma; Ibrahim, Maznah (Serials Publiations, 2010)
It is generally believed that Malaysia achieves its economic growth due to the cheap labor supplied by low-skilled foreign migrant workers. However, some believed that they have been exploited and their rights as workers have been ignored, i.e., they have worked in a poor working environment and lived in a poor condition. This study therefore seekd to reveal the micro data of the current status of foreign migrant workers in Malaysia by examining their working environment and living condition in a selected geographical area in Kuala Lumpur, Malaysia. In general, the results indicate that most of the foreign migrant workers feel comfortable working at their workplace and they perceived the living condition is conducive. Among the suggestions to improve further the working environment and living conditions of the foreign migrant workers are by establishing the memorandum of understanding between countries and by adopting a comprehensive legislative approach.